Product improvement and storage study of soft rolls - Santos, Maria Rowena Quezada; Mateo, Liwayway T. (1993.)
This study was undertaken with the main objective of improving a given formulation of soft rolls (in the form of hamburger buns). A preliminary study was conducted to identify the product attributes that require improvement. The hamburger buns were characterized as having a dry mouthfeel and a yeasty aroma as indicated by the results of the sensory evaluation. In Phase I, two subphases were created to improve the formulation of hamburger buns. In Phase IA, the optimum glucose syrup: sugar concentration was determined. The most favorable concentration was found to be that containing 3% glucose syrup and 11.5% sugar based on the results of the subjective tests. The addition of glucose syrup at any concentration did not significantly affect either the bread weight, volume, or specific volume, however, the crumb structure was markedly improved over the original formulation. The results in Phase IB revealed that the optimum shortening level was 6.5% as indicated by the results of the sensory evaluation. Similarly, adjustments of the shortening level did not significantly affect any of the quality attributes as well as the overall acceptability except for the mouthfeel, where at shortening level of 6.5% it was considered to be very smooth. In Phase II, the shelf-life of both the original and the improved hamburger bun formulations was studied. Based on the results of the tests, as analyzed by the ANOVA and DMRT, the improved formulation can retain its favorable eating characteristics until the 7th day of storage, and it was given a rating of liked slightly. However, the hamburger buns containing glucose syrup underwent a rapid increase in crumb firmness as seen from the compressibility measurements and texture ratings. Based on all tests done, the improved product has a shelf-life of 7 days at room temperature with its quality characteristics still intact and perceptible.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Bread